2011
DOI: 10.4236/wja.2011.12003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cognitive Behavioral Therapy and Changes of Depressive Symptoms Among Thai Adult HIV-Infected Patients

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The result revealed that the use of CBT led to a reduction in the levels of depression, anxiety, and stress of the participants. This was in line with the findings of Hamzeh Pour (2014); Hoffman and Smits ( 2008); Hollon et al (2006); Jayasvasti et al (2011); Momeni et al (2010); Riper et al (2014);and Watkins et al (2011). The researchers reported that CBT, whether of individuals or groups, was effective in reducing depression.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The result revealed that the use of CBT led to a reduction in the levels of depression, anxiety, and stress of the participants. This was in line with the findings of Hamzeh Pour (2014); Hoffman and Smits ( 2008); Hollon et al (2006); Jayasvasti et al (2011); Momeni et al (2010); Riper et al (2014);and Watkins et al (2011). The researchers reported that CBT, whether of individuals or groups, was effective in reducing depression.…”
Section: Discussionsupporting
confidence: 85%
“…Concerning the comorbidity of depression and anxiety with addiction, three factors can be simultaneously solved through CBT. Results of studies by Hamzeh Pour (2014); Hoffman and Smits (2008); Hollon, Stewart, and Strunk (2006); Jayasvasti et al (2011); Momeni et al (2010); Riper et al (2014); Toneatto and Calderwood (2015); and Watkins et al (2011) reveal that CBT can be effective in reducing depression and anxiety. Furthermore, researchers have also shown that CBT can reduce stress, anxiety, and depression in people with addiction (McHugh et al, 2010;Osilla, Hepner, Muñoz, Woo, & Watkins, 2009;Sugarman, Nich, & Carroll, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous study demonstrated that CBT is an effective intervention in reducing depression, anxiety, and perceived stress. [ 19 ] Jayasvasti et al [ 20 ] reported that cognitive behavioral program is beneficial for treatment of depression among adult HIV-infected patients. CBT is a treatment approach that addresses dysfunctional emotions, maladaptive behaviors, cognitive processes, and contents.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations resulting from an immunodefi ciency condition due to HIV infection are associated with complex medical, psychological and social implications that arise at diff erent times, from diagnosis to treatment, and require relevant adaptive eff orts from people living with HIV -PLH (Dalmida, Koenig, Holstad, & Thomas, 2015;Jayasvasti et al, 2011;Seidl & Faustino, 2014;Yu, Lau, Mak, Cheng, & Zhang, 2014). Despite the biopsychosocial damage associated with HIV/ AIDS infection, many PLHA can avoid and overcome the impacts living with HIV/AIDS has on them and rebuild their lives (Wiegers, 2008).…”
Section: Resiliencia De Personas Con Hiv/aids: Infl Uencia Del Copingmentioning
confidence: 99%